Answer:
To solve the system below by substitution, replace y in the second equation with 7−6x.
==> False
This statement is false. To solve the system by substitution, replace x in the second equation with 7−6x.
==> False.
This statement is false. To solve the system by substitution, replace y in the first equation with 7−6x.
==> False
This statement is false. To solve the system by substitution, replace y in the second equation with 6x−7.
==> True.
<em>From</em><em> </em><em>the</em><em> </em><em>first</em><em> </em><em>equat</em><em>ion</em><em>,</em><em> </em><em>6</em><em>x</em><em>-</em><em>y</em><em>=</em><em>7</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>y</em><em>=</em><em> </em><em>6</em><em>x</em><em>-</em><em>7</em>